2000
DOI: 10.1107/s0108270100004340
|View full text |Cite
|
Sign up to set email alerts
|

Pefloxacinium methanesulfonate 0.10-hydrate

Abstract: The crystal structure of 4-(3-carboxy-1-ethyl-6-¯uoro-1,4dihydro-4-oxo-7-quinolyl)-1-methylpiperazinium methanesulfonate 0.10-hydrate, C 17 H 21 FN 3 O 3 + ÁCH 3 O 3 S À Á0.10H 2 O, contains pe¯oxacinium cations, methanesulfonate anions and a partially occupied water of solvation. The quinoline ring system in the cation is essentially planar. The anions lie parallel to each other about inversion centers. The structure is stabilized by strong hydrogen bonds involving the terminal piperazinyl-N atom of the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…The main bond lengths and valence angles are shown in Table 1S. They coincide with those found earlier for 1 and given in the literature for ions PefH2 + [21][22][23][24] and Htba − [25][26][27][28][29].…”
Section: Crystal Structures Of (2)supporting
confidence: 71%
See 1 more Smart Citation
“…The main bond lengths and valence angles are shown in Table 1S. They coincide with those found earlier for 1 and given in the literature for ions PefH2 + [21][22][23][24] and Htba − [25][26][27][28][29].…”
Section: Crystal Structures Of (2)supporting
confidence: 71%
“…Similar to 1, the structures pefloxacinium methanesulfonate hydrates [22,23] The π-π interaction in 1 combines pefloxacinium сations to the pairs (Table 3S, Fig. 3Sa).…”
Section: Crystal Structures Of (1)mentioning
confidence: 99%
“…In accordance with the crystal structure of ciprofloxacin hexahydrate, [21] the authors have concluded that the carboxylic group is deprotonated and the molecule exists in zwitterionic form [22]. The ionic carboxylates [23] show no carbonyl stretching at about 1700 cm À1 , but have two attributed bands in the range of 1650-1510 cm À1 and 1460-1400 cm À1 that could be assigned as (O-C-O) asymmetric and symmetric stretching vibrations. In the spectrum of gatifloxacin sesquihydrate the (O-C-O) a + (C@O) p band appears at 1600-1658 with maxima at 1638 cm À1 , (O-C-O) s band stretch at 1398 cm À1 and C-O absorbs at 1282 cm À1 .…”
Section: Infrared Absorption Studiesmentioning
confidence: 65%
“…All calculations use the Gaussian 09 electronic structure package . We benchmarked semi‐empirical and DFT geometry approximations to 12 fluoroquinolone and 6 quinolone experimental XRD crystal structures . Hydrogen atoms were added in GaussView 5.0, as the experimental hydrogen atom positions were not reported.…”
Section: Methodsmentioning
confidence: 99%